Implementation of E-Module in Indonesia EFL Higher Education: A Literature Review - Sutrisno Sadji Evenddy; Nurhaeda Gailea; Syafrizal Syafrizal (IJORER : International Journal of Recent Educational Research, 2024)
Objectives: This study aims to identify trends, patterns, and challenges in the research regarding using e-modules in teaching English at the higher education level in Indonesia. Method: This qualitative study employs a literature review method based on articles from Google Scholar about implementing e-modules in Indonesian EFL higher education from 2021 to 2023. The author uses inductive reasoning to analyze the research data, integrating findings from previous studies on using e-modules in Indonesian EFL higher education. Result: The general trend is a strong emphasis on developing and validating e-modules and other digital tools to enhance various language skills, especially critical thinking, writing, and listening. The tools are being integrated with technology and used in diverse educational contexts, with university students being the primary beneficiaries. Research methods predominantly involve R&D, reflecting a focus on the creation and assessment of new educational interventions. Future research should deepen our understanding of the long-term impact, effectiveness, and scalability of e-modules in diverse educational contexts. Novelty: Although there is substantial literature on the use of e-modules in English language learning, there is a notable scarcity of research specifically addressing the trends in e-module implementation within Indonesian higher education institutions